Diluent-mediated interfacial reactions in localized-high-concentration electrolytes for fast-charging lithium-ion batteries - Park, Seungsoo; Chang, Hongjun; Lee, Hyuntae; Lim, Minhong; An, Hyeongguk; Kang, Jiwoong; Lee, Soyeon; Lee, Mingyu; Han, Cheolhee; Lee, Hochun; Chae, Sujong; Moon, Janghyuk; et al. (Journal of materials chemistry. A, Materials for energy and sustainability, 2024)
Reframing ionic transport and interface chemistry through electrolyte renovation is essential to promote the fast charging of Li-ion batteries, even under extreme conditions. Despite the formation of a less resistive interface using high-concentration electrolytes (HCEs), their inevitably high viscosity compromises their practical use. This work aims to explore the most suitable hydrofluoroether diluents for localized-high-concentration electrolytes (LHCEs). Contrary to the consensus on their negligible intervention in the Li + solvation sheath, experimental evidence, and simulation studies have revealed that diluents can partially penetrate solvation and enable intermolecular interactions with solvents and additives. While the extent of physical intervention is similar, the intermolecular binding becomes greater when using longer-chain diluents with increased -CF 2 - moieties, hindering the desired interfacial reactions. By strategically selecting smaller diluents with fewer -CF 2 - units, low-viscosity LHCEs can attain the long stable cycling of Li-ion cells at a 10 minute charging rate (∼18 mA cm −2 ) over 500 cycles, and facilitate reliable performance under demanding conditions, such as thick electrodes (∼5 mAh cm −2 ) and low temperatures (−20 °C). The "marionette" effect of various diluents in localized-high-concentration electrolytes subtly controls solvent and additive interactions and refines interfacial chemistry for enhancing Li-ion battery performance, particularly in extreme conditions.